Development and reliability of a hand-held dynamometer device to measure the ankle dorsiflexor muscle strength - Kimura, Masanobu; Ogata, Yuto; Akebi, Toru; Ochi, Mitsuhiro; Hachisuka, Kenji; Saeki, Satoru (Journal of Rehabilitation and Assistive Technologies Engineering, 2018)
Background Ankle dorsiflexor muscle strength is a crucial component of gait. Objective We describe the development of a simple, hand-held dynamometer to measure the ankle dorsiflexor muscle strength in the sitting position. In addition, we examine its intra- and inter-rater reliability. Methods Measurements of the peak ankle dorsiflexor muscle strength were obtained by two examiners for 30 ankles of 15 healthy adults at two time points, with a one-day interval between measurements, to determine the inter- and intra-rater reliability. The intraclass correlation coefficients were calculated, and an intraclass correlation coefficient > 0.90 was considered as excellent reliability. A Bland–Altman analysis was used to assess systemic bias. The minimal detectable change in muscle strength was calculated with a confidence level of 95% (MDC95). Results The reliability of the device was excellent for both intra- (intraclass correlation coefficients [1,3] = 0.94) and inter-rater (intraclass correlation coefficients [2,3] = 0.96) comparisons. No fixed or proportional bias was observed between the two examiners. The MDC95 was 0.77 N/kg. Conclusions Our results indicate the excellent reliability and responsiveness of our device. By obtaining the measurements of dorsiflexor strength while sitting, compensatory motions are suppressed, yielding a more consistent measurement that can be reliably used to detect subtle changes in the ankle dorsiflexor muscle strength.